Une communauté désenchantée ? Métamorphoses du merveilleux dans le roman contemporain pour adolescents - Laurent Bazin (Strenae)
Contemporary young adult novels resort to the universe of classical tales, playing with these older structures and characters while revisiting them within the generic framework of today's fiction. This intertextual game, which constitutes an homage to the classical pantheon by drawing on collective memory to reinforce the heroes’ appeal, subverts codes in the patrimonial culture to better narrate a search for meaning and the problematic quest for identity characteristic in modern societies.